2011
DOI: 10.3844/jcssp.2011.1605.1611
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neuro-Fuzzy Techniques for Solar Radiation

Abstract: Problem statement:The prediction is very useful in solar energy applications because it permits to estimate solar data for locations where measurements are not available. The developed artificial intelligence models predict the solar radiation time series more effectively compared to the conventional procedures based on the clearness index. Approach: The forecasting ability of some models could be further enhanced with the use of additional meteorological parameters. After having simulated many different struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The results showed that ANN and ANFIS intelligent models are the powerful tools in prediction of GSR for the selected stations, but prediction by ANN was found to be more accurate than ANFIS [34]. Rahoma et al (2011) used ANFIS for SR estimation. They can prove that the combination of linguistic rules of FL with the training algorithm used in neural networks contributes in very qualitative prediction results, which approach the 'best' neural predictor's results [61].…”
Section: Ann Model An Ann Is a Collection Of Electrical Neurons (mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that ANN and ANFIS intelligent models are the powerful tools in prediction of GSR for the selected stations, but prediction by ANN was found to be more accurate than ANFIS [34]. Rahoma et al (2011) used ANFIS for SR estimation. They can prove that the combination of linguistic rules of FL with the training algorithm used in neural networks contributes in very qualitative prediction results, which approach the 'best' neural predictor's results [61].…”
Section: Ann Model An Ann Is a Collection Of Electrical Neurons (mentioning
confidence: 99%
“…Rahoma et al (2011) used ANFIS for SR estimation. They can prove that the combination of linguistic rules of FL with the training algorithm used in neural networks contributes in very qualitative prediction results, which approach the 'best' neural predictor's results [61].…”
Section: Ann Model An Ann Is a Collection Of Electrical Neurons (mentioning
confidence: 99%
“…In fact, these models presume that maximum temperature will decrease with reduced transmissivity, whilst minimum temperature will increase because of the cloud emissivity. Clear skies will increase maximum temperature due to higher shortwave radiation during sunshine hours, and minimum temperature will decrease due to higher transmissivity at night times; so the difference between daily maximum and minimum air temperatures becomes an indicator of cloudiness (Almorox et al, 2013) Estimating the horizontal global solar radiation using different artificial and computational intelligence techniques including the artificial neural network (ANN) (Tymvios et al 2005;Mubiru and Banda 2008;Şenkal and Kuleli 2009;Solmaz and Ozgoren, 2012), particle swarm optimization (PSO) (Mohandes, 2012), adaptive neuro-fuzzy inference system (ANFIS) (Mellit et al 2007;Rahoma et al, 2011;Sumithira and Kumar, 2012;Güçlü et al, 2014;Mohanty et al, 2015;Mohammadi et al, 2015a), support vector machine (SVM) (Chen et al, 2013;Mohammadi et al, 2015b;Mohammadi et al, 2015c), and etc. has received tremendous attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the excessive computational load of the usual statistical predictiontechniques hardly find acceptance within the technology transfer for the production of devices hospital monitoring.In recent years, the soft computing prediction techniques have been worked out with excellent results both in theoretical and applicative fields. In particular, remarkable results have been obtained by fuzzy and neuro-fuzzy techniques (Rahoma et al, 2011) by means of the construction of banks of naive fuzzy rules or with more sophisticated techniques of extraction of inferences directly from numerical data with the undoubted advantage of creating linguistic structures easily modifiable and/or updateable by the knowledge of the expert. However, since ICP depends on several patho-physiological factors, the structuring of the banks of fuzzy rules may be often complicated with obvious problem of explosion of the number of the rules for which it is necessary to drastically reduce the number of inputs.…”
Section: Introductionmentioning
confidence: 99%